A study on the ecological philosophy of Laozi - Zhicheng Wang (HTS Teologiese Studies/Theological Studies, 2023)
The eco-environmental problems have become a hot topic of global concern today. Many scholars seek intellectual resources from traditional cultures to solve these problems. This article tries to extract the rich ecological thoughts from the text of Laozi. According to Laozi, Tao is ‘the mother of all beneath Heaven’, that is, the whole universe, including man and nature, evolve from Tao. This indicates the primary harmony of man and nature. However, man mistakenly regards himself as the lord of nature, and uses his force and methods of science and technology to enslave nature, causing the current ecological crisis. The way to resolve the crisis is pointed out in the following statement: ‘Man should imitate Earth, Earth should imitate Heaven, Heaven should imitate Tao, and Tao is being what it is’. Laozi advocates man to imitate nature, leading a life of ‘having no self’, ‘wu wei’ or ‘desiring no-desire’. This is the Tao-centred way of living, which brings about a transformation in human existence.